Increased Protein Synthesis by Human Platelets during Phagocytosis of Latex Particles in Vitro - Bessler, Hana; Agam, Galila; Djaldetti, Meir (Thrombosis and Haemostasis, 1976)
A three-fold increase of protein synthesis by human platelets during in vitro phagocytosis of polystyrene latex particles was detected. During the first two hours of incubation, the percentage of phagocytizing platelets and the number of latex particles per platelet increased; by the end of the third hour, the first parameter remained stable, while the number of latex particles per cell had decreased.Vincristine (20 μg/ml of cell suspension) inhibited platelet protein synthesis. This effect was both time- and dose-dependent. The drug also caused a decrease in the number of phagocytizing cells, as well as in their phagocytotic activity.